The Utilization of Two Commercial Indonesian Fertilizers as Microalgal Growth Medium for Chlorella pyrenoidosa and Botryococcus braunii Cultivation - Widyatama, Awang; Al Fajry, Zaidan; Widyatama, Satria Aqilla; Mulyati, Ade Heri; Stiawan, Elva (Jurnal Kartika Kimia, 2024)
In the current trend of the upstream stage of microalgal bioprocessing studies, many works mainly focused on optimizing microalgal cultivation parameters for obtaining a high yield of either biomass or a particular metabolite. Meanwhile, efforts to alternatively provide affordable growth medium are considered still limited to be performed. This study aims to provide an alternative microalgal growth medium from commercial fertilizers and supplements provided by a particular Indonesian company. Our proposed microalgal growth medium was developed by considering the chemical contents of the products with the essential components of an established Guillard f/2 microalgal growth medium. By employing the developed growth medium in Chlorella pyrenoidosa and Botryococcus braunii cultivation, similar growth profiles were shown in both green microalgae with optimum time for biomass harvesting encouraged within two weeks of cultivation. Regarding biomass productivity, 0.19 g and 0.20 of dried biomass were averagely obtained from 1 L cultures of Chlorella pyrenoidosa and Botryococcus braunii, respectively. This finding implies that two Indonesian fertilizer products could be utilized as the main ingredient of moderate performance of green microalgal growth medium.